Effect of Two Unique Nanoparticle Formulations on the Efficacy of a Broadly Protective Vaccine Against Pseudomonas Aeruginosa - Howlader, Debaki R.; Das, Sayan; Lu, Ti; Hu, Gang; Varisco, David J.; Dietz, Zackary K.; Walton, Sierra P.; Ratnakaram, Siva Sai Kumar; Gardner, Francesca M.; Ernst, Robert K.; Picking, William D.; Picking, Wendy L. (Frontiers in Pharmacology, 2021)
Pseudomonas aeruginosa is an opportunistic pathogen responsible for a wide range of infections in humans. In addition to its innate antibiotic resistance, P. aeruginosa is very effective in acquiring resistance resulting in the emergence of multi-drug resistance strains and a licensed vaccine is not yet available. We have previously demonstrated the protective efficacy of a novel antigen PaF (Pa Fusion), a fusion of the type III secretion system (T3SS) needle tip protein, PcrV, and the first of two translocator proteins, PopB. PaF was modified to provide a self-adjuvanting activity by fusing the A1 subunit of the heat-labile enterotoxin from Enterotoxigenic E. coli to its N-terminus to give L-PaF. In addition to providing protection against 04 and 06 serotypes of P. aeruginosa, L-PaF elicited opsonophagocytic killing and stimulated IL-17A secretion, which have been predicted to be required for a successful vaccine. While monomeric recombinant subunit vaccines can be protective in mice, this protection often does not transfer to humans where multimeric formulations perform better. Here, we use two unique formulations, an oil-in-water (o/w) emulsion and a chitosan particle, as well as the addition of a unique TLR4 agonist, BECC438 (a detoxified lipid A analogue designated Bacterial Enzymatic Combinatorial Chemistry 438), as an initial step in optimizing L-PaF for use in humans. The o/w emulsion together with BECC438 provided the best protective efficacy, which correlated with high levels of opsonophagocytic killing and IL-17A secretion, thereby reducing the lung burden among all the vaccinated groups tested.